Dynamics of microbial community structure and function in a tallgrass prairie ecosystem - Veach, Allison Michelle (Kansas State University, 2015)
Due to agricultural practices and urbanization, tallgrass prairie ecosystems have become threatened as < 5% of its historical coverage exists today. The small remainder of praire that does exist is further threatened by the encroachment of woody plant species. Woody plant encroachment may not only alter prairie ecosystem function, but also prairie microbial communities responsible for these functional processes. Further, prairies are high disturbance ecosystems, especially prairie streams which are hydrologically harsh. They support communities that frequently undergo succession due to recurring flood and drought conditions, yet little is known about the response of microbial communities to these disturbances. In my dissertation, I first address the degree of woody vegetation expansion in riparian corridors (parallel to streams) in watersheds with variable fire frequency and grazing. I found that the rate of riparian woody expansion declines with higher fire intervals and is not affected by grazing, but even annual burns may not prevent woody plant expansion in riparian zones from occurring. Second, I quantified the effect of using restorations of riparian corridors, through removal of woody plants, on physical, chemical, and microbial community (bacteria and fungi) dynamics across stream to upslope soils. Removal restoration causes a decrease in NH₄⁺ and soil water content, and causes streams and upslope soils to become similar in fungal community richness unlike forested landscapes. Bacterial communities were minimally impacted by removals, but were highly structured among stream to upslope soils due to multiple environmental gradients (i.e., pH, NO₃⁻, soil moisture). Lastly, I examined the successional development of biofilm-associated microbial communities in a prairie stream from both a functional and structural perspective. I found that biofilm microbes exhibited strong successional trajectories, with communities developing towards net autotrophy and therefore becoming reliant upon in-stream derived carbon. Further, bacterial communities displayed spatial differences, but much stronger temporal patterns in community composition were detected. These studies highlight how woody plant encroachment may influence stream ecosystems in addition to spatiotemporal trends in microbial community assembly.
Keywords: Microbial communities; Woody encroachment; Bacteria; Fungi; Biofilms; Stream; Biology (0306); Ecology (0329)